The Effect of Financial Literacy and Paylater Payment System on Student Consumptive Behavior in Ciamis Regency in Sharia Economic Perspective - Engkar Rahma Maulida; Eris Munandar; Nila Nurochani (CV. Rayyan Dwi Bharata, 2023)
Financial literacy is a knowledge that everyone should know and understand, not just to manage income but to manage their finances well. More and more e-commerce that provide various kinds of payment systems, for example paylater, this is also a reason that someone must understand financial literacy. Students are synonymous with life that follows trends and likes to shop online which in turn causes consumptive behavior because they do not know how to manage finances properly. Therefore, financial literacy is essential for students when facing individual or group financial problems, but its implementation in everyday life will be even better. From this background, this research was conducted with the title